The Correlation Between Students Scanning Technique And Their Reading Comprehension At SMAN 7 Manado - Nofry Frans; Tabita Astanto; Vera Wahani (Journal of Innovative and Creativity, 2025)
This study aimed to examine the relationship between students’ use of scanning strategies and their reading comprehension performance at SMAN 7 Manado. Employing a quantitative descriptive research design, data were collected from Grade 10 students and analyzed using descriptive statistics and the Pearson Product-Moment Correlation Coefficient. The results showed that the mean score of students’ scanning strategy was 2.63, indicating a moderate level, while their reading comprehension performance had a mean score of 3.40, also categorized as moderate. Statistical analysis revealed a significant correlation between the two variables, with a p-value of 0.000 and a correlation coefficient (r) of 0.639, signifying a strong positive relationship. These findings suggest that students’ proficiency in scanning strategies is significantly associated with their reading comprehension outcomes.